PLANNING OF INTEGRATED WASTE PROCESSING SITE (TPST) IN LHOKNGA DISTRICT, ACEH BESAR REGENCY - Mubarak, Fathul (Indonesian Journal of Environmental Sustainability, 2025)
Waste management remains a critical issue in Lhoknga Sub-district, Aceh Besar, due to limited facilities, inadequate collection systems, and low community participation. This study aims to plan an Integrated Waste Processing Facility (TPST) as a sustainable long-term waste management solution. A quantitative approach was applied through waste generation and composition sampling over eight consecutive days in accordance with SNI 19-3964-1994, covering both domestic and non-domestic sources. Fishbone analysis was employed to identify key factors influencing waste management performance. The findings indicate that organic waste, particularly food waste, dominates the waste composition. The proposed TPST is designed to manage 83.78 m³/day of waste projected until 2043, based on national standards and regional planning policies. This study contributes scientifically by offering a data-driven TPST planning framework that can be replicated in coastal and tourism-oriented regions facing similar waste management challenges.